The integration of black trainees into the organisational culture of audit firms in JHB SA - Phake, Welhermina Ntsetse (My University, 2017)
The legacy of apartheid in South Africa is still evident in the corporate environment even 23 years into our democracy. The Black Economic Empowerment Act (BEE) was enacted into law in 1998, and later amended in 2013 to the Broad Based Black Economic Empowerment Act (BBBEE), to redress the inequalities in representation in the workplace and to give black people meaningful participation in the economy. The Chattered Accountancy profession has made strides in complying with legislation when it comes to transforming the industry. The CA charter was drafted and signed in 2011 to serve as a guide for SAICA member firms and other partners in growing the number of blacks in the CA profession. An educational development program, Thuthuka, was introduced by SAICA to manage and fund skills development initiatives for black students pursuing the CA qualification. The establishment of organizations such as the Association for the Advancement of Black Accountants of Southern Africa (ABASA) and The African Women Chartered Accountants Forum (AWCA) has also pushed progress on the advancement of the previously excluded groups; black people and women, in this industry. SAICA 2017 statistics show 4725 registered black accountants, while the number sits at 30842 for white accountants in March that year. The stats also show that black trainees have the lowest pass rate for the qualifying exams. The number of black trainees taking the qualifying exams has been increasing year on year, and more firms are taking on more black trainees for articles. There is evident progress in what has been done, and what is currently being done to advance the number of qualified black accountants. However, much like the issue with BBBEE legislation countrywide, there is no evidence of a culture integration within the industry to include black trainees. A qualitative study was conducted to determine the progress, if any, of integrating black trainees in the organizational culture of audit firms. Several trainees currently in articles at the big four audit firms in Johannesburg are interviewed to record their perceptions of organizational culture and whether or not they feel a part of that culture, without having to assimilate. The study also investigates whether the perception of inclusion affects their decision to stay on post their articles. The study found that there are varying perspectives to what people consider organizational culture. It also found some new themes such as involvement in decision making, communication, technical knowledge and diversity that black trainees value as more important when it comes to their integration in their training programs. However, these dimensions according to Hofstede framework assist in assessing the type of organisational culture at the firms which are being studied or may assist in building a strategy of creating or moving towards a certain desired culture. Thus, the research used the framework to determine what and how organisational culture is taking place in audit firms in JHB with reference to KMPG, Ernst & Young, Deloitte and Pricewaterhouse Coopers). The results depict that indeed there is need of incorporating black trainees in the shaping of organizational cultures going forward. Furthermore, the results indicate that the respondents do not attribute the cultures in their relative organizations as a factor on their performance. The study contributes to the human resource practitioners and managers in the accounting industry who want to establish and advance diversity programs within their organisations. The study also adds value to audit supervisors who want to promote progressive work relationships with their trainees.
MBA
Keywords: Organizational change. Auditing -- South Africa. Career development